Though active on RINm5F insulinoma cells and cultured pancreatic islets, recombinant IL-22 fails to modulate cytotoxicity and disease in a protocol of streptozotocin-induced experimental diabetes. - Anika eBerner; Malte eBachmann; Christine eBender; Josef ePfeilschifter; Urs eChristen; Heiko eMühl (Frontiers Media S.A., 2016)
Interleukin (IL)-22 is a cytokine displaying tissue protective and pro-regenerative functions in various preclinical disease models. Anti-bacterial, pro-proliferative, and anti-apoptotic properties mediated by activation of the transcription factor signal transducer and activator of transcription (STAT)-3 are key to biological functions of this IL-10 family member. Herein, we introduce RINm5F insulinoma cells as rat ß-cell line that, under the influence of IL-22, displays activation of STAT3 with induction of its downstream gene targets Socs3, Bcl3, and Reg3ß. In addition, IL-22 also activates STAT1 in this cell type. To refine those observations, IL-22 biological activity was evaluated using ex vivo cultivated murine pancreatic islets. In accord with data on RINm5F cells, islet exposure to IL-22 activated STAT3 and upregulation of STAT3-inducible Socs3, Bcl3, and STEAP4 was evident under those conditions. As these observations supported the hypothesis that IL-22 may exert protective functions in toxic ß-cell injury, application of IL-22 was investigated in murine multiple-low-dose streptozotocin (STZ)-induced diabetes. For that purpose, recombinant IL-22 was administered thrice either immediately before and at disease onset (at d4, d6, d8) or closely thereafter (at d8, d10, d12). These two IL-22-treatment periods coincide with two early peaks of ß-cell injury detectable in this model. Notably, none of the two IL-22-treatment strategies affected diabetes incidence or blood glucose levels in STZ-treated mice. Moreover, pathological changes in islet morphology analyzed 28 days after disease induction were not ameliorated by IL-22 administration. Taken together, despite being active on rat RINm5F insulinoma cells and murine pancreatic islets, recombinant IL-22 fails to protect pancreatic ß-cells in the tested protocols from toxic effects of STZ and thus is unable to ameliorate disease in the widely used model of STZ-induced diabetes.